2012
DOI: 10.1177/0269216312455729
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year literature review of family caregiving for motor neurone disease: Moving from caregiver burden studies to palliative care interventions

Abstract: Background: There is growing awareness that different terminal diseases translate into different family caregiver experiences, and the palliative and supportive care needs of these families are both similar and unique. Family members caring for people with motor neurone disease may experience exceptional strain due to the usually rapid and progressive nature of this terminal illness. Aim: The purpose of this review is to synthesize contemporary research and provide a comprehensive summary of findings relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 82 publications
6
135
1
7
Order By: Relevance
“…Caring for a family member can have a significant physical, social, emotional, and financial impact on those who care (1,2). Family carers in ALS encounter caregiver burden (3,4) and caregiver burden can have an adverse effect on their wellbeing (5). Caregiver burden in ALS increases with disease duration (6) and is higher among those who care for patients who have behavioural impairment (7).…”
Section: Introductionmentioning
confidence: 99%
“…Caring for a family member can have a significant physical, social, emotional, and financial impact on those who care (1,2). Family carers in ALS encounter caregiver burden (3,4) and caregiver burden can have an adverse effect on their wellbeing (5). Caregiver burden in ALS increases with disease duration (6) and is higher among those who care for patients who have behavioural impairment (7).…”
Section: Introductionmentioning
confidence: 99%
“…Six studies intended to examine the influence of gender, skills, experiences and needs of carers in their home environment and two studies tried to do it in a hospital setting [6,[14][15][16][17][18]. One study reported caregivers experiences with ventilated patients at home, and other showed the evidence of caring for patients with Amyotrophic Lateral Sclerosis (ALS) [12,19] Four studies did not specify the setting of care where the patient was during the data collection [9,13,16,17,[20][21][22], and four did not make reference to the fact that the patient was followed or not by a PC team.…”
Section: Resultsmentioning
confidence: 99%
“…The same review alerted to the fact that most of the studies in this area were focused on the description of the profile of these family carers, instead of focusing on the development of interventions aiming to assist the caregivers to cope with their everyday emotions, instrumental and spiritual issues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Carers have substantial involvement in ALS patient care [17] and value patients' autonomy over their choices [10]. As well as offering emotional and logistical support, carers promote patient autonomy through synthesis of ALS health information and advocacy in healthcare appointments [10].…”
Section: Carer Inclusionmentioning
confidence: 99%
“…However, carer participation in decisionmaking and advocacy is moderated by the high burden and distress they experience [17]. Similar to health professionals, carers may find themselves torn between respect for patient autonomy and supporting patient participation in care.…”
Section: Carer Inclusionmentioning
confidence: 99%